Effects of the two types of anorexia nervosa (binge eating/purging and restrictive) on bone metabolism in female patients. (25th April 2018) - Maïmoun, Laurent; Guillaume, Sébastien; Lefebvre, Patrick; Bertet, Helena; Seneque, Maude; Philibert, Pascal; Picot, Marie‐Christine; Dupuy, Anne‐Marie; Paris, Françoise; Gaspari, Laura; Ben Bouallègue, Fayçal; Courtet, Philippe; et al.
Summary: Objective: This study compared the profiles of the two types of anorexia nervosa (AN; restrictive: AN‐R, and binge eating/purging: AN‐BP) in terms of body composition, gynaecological status, disease history and the potential effects on bone metabolism. Design: Two hundred and eighty‐six women with AN (21.8 ± 6.5 years; 204 AN‐R and 82 AN‐BP) and 130 age‐matched controls (CON; 22.6 ± 6.8 years) were enrolled. Areal bone mineral density (aBMD) was determined using DXA and resting energy expenditure (REE) was indirectly assessed using calorimetry. Markers of bone formation (osteocalcin [OC], procollagen type I N‐terminal propeptide [PINP] and resorption (type I‐C telopeptide breakdown products [CTX]) and leptin were concomitantly evaluated. Results: Anorexia nervosa patients presented an alteration in aBMD and bone turnover. When compared according to type, AN‐BP were older than AN‐R and showed less severe undernutrition, lower CTx levels, longer duration of AN, and higher REE levels and aBMD at radius and lumbar spine. After adjustment for age, weight and hormonal contraceptive use, the aBMD and CTx differences disappeared. In both AN groups, aBMD was positively correlated with anthropometric parameters and negatively correlated with durations of AN and amenorrhoea, the bone formation markers (OC and PINP) and the leptin/fat mass ratio. REE was positively correlated with aBMD in AN‐R patients only. Conclusions: This study shows the profiles of AN patients according to AN type. However, the impact of the profile characteristics on bone status, although significant, was minor and disappeared after multiple adjustments. The positive correlation between REE and aBMD reinforces the concept that energy disposal and bone metabolism are strongly interdependent.